2008
DOI: 10.1177/193229680800200202
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Monitoring in Acute Care: Technologies on the Horizon

Abstract: Current glucose monitoring technology appears inadequate for the management of diabetic surgical and in critically ill patients requiring intensive insulin therapy. Subcutaneous sensors measure interstitial fluid glucose, and this technology has not yet been shown to provide the timely and accurate measurements necessary for intravenous insulin administration in surgical and critical care patients on intensive insulin therapy. Technologies under development that may be more suitable for surgical and intensive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 38 publications
(1 reference statement)
0
11
0
Order By: Relevance
“…As predicted by the World Health Organization (WHO), the number of diabetes patients has been gradually increasing [147], and such patients require the continuous monitoring of glucose levels in the interstitial fluid. Currently, only invasive methods are available for monitoring the glucose in the blood [148,149,150]. Lipani et al demonstrated a noninvasive, transdermal, path-selective, and specific glucose monitoring and detection system based on a miniaturized device array platform fabricated by a graphene thin-film method or screen-printing technology [151].…”
Section: Electronic Properties and Applicationsmentioning
confidence: 99%
“…As predicted by the World Health Organization (WHO), the number of diabetes patients has been gradually increasing [147], and such patients require the continuous monitoring of glucose levels in the interstitial fluid. Currently, only invasive methods are available for monitoring the glucose in the blood [148,149,150]. Lipani et al demonstrated a noninvasive, transdermal, path-selective, and specific glucose monitoring and detection system based on a miniaturized device array platform fabricated by a graphene thin-film method or screen-printing technology [151].…”
Section: Electronic Properties and Applicationsmentioning
confidence: 99%
“…89 Clinicians in the future may utilize this near-continuous glucose monitoring system to perform a prospective randomized clinical trial to determine whether clinical outcome can be improved (decreased morbidity, mortality, length of stay, and hospital cost) as a result of optimized insulin therapy and BG control (avoidance of hyperglycemia, hypoglycemia, and glycemic variability). 61,79,90 A nearcontinuous IV glucose monitoring system that is safe, accurate, reliable, and user-friendly has great potential to be integrated with a computer controller and infusion pumps for IV insulin and IV glucose to produce a closed-loop in-hospital artificial pancreas.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of which method is used, the process is laborintensive 27,28 and a recognized limitation to the practice of IIT. [29][30][31][32] Availability of an in-hospital automated BG monitor could facilitate implementation of IIT protocols through more effective titration of insulin therapy, improved BG control, and avoidance of hypoglycemia.…”
Section: Introductionmentioning
confidence: 99%